Characterization of Corn Starch Films Reinforced with CaCO(3) Nanoparticles - Sun, Qingjie (Public Library of Science, 2014)
The characterization of corn starch (CS) films impregnated with CaCO(3) nanoparticles was investigated. Criteria such as morphology, crystallinity, water vapor permeability (WVP), opacity, and mechanical properties were the focus of the investigation. It was found that the CaCO(3) contents had significant effects on the tensile properties of the nanocomposite films. The addition of CaCO(3) nanoparticles to the CS films significantly increased tensile strength from 1.40 to 2.24 MPa, elongation from 79.21 to 118.98%, and Young’s modulus from 1.82 to 2.41 MPa. The incorporation of CaCO(3) nanoparticles increased the opacity of films, lowered the degree of WVP and film solubility value compared to those of the CS films. The results of scanning electron microscopy (SEM) showed that with the increase of CaCO(3) nanoparticles content in starch films, the roughness of the films increased, and pores or cavities were found on the surface of the films, while small cracks were observed in the structures of the fractured surfaces. X-ray diffraction showed that the addition of nanoparticles increased the peaks in the intensity of films.